Implementation of Early Childhood Character Education at TK Pembina 4 Ogan Komering Ulu - Mellina, Vellia; Arafat, Yasir; Puspita, Yenny (Yayasan Sembilan Pemuda Indonesia, 2024)
This study aims to describe the implementation of early childhood character education in TK Pembina 4 Ogan Komering Ulu. This research uses qualitative methods with a descriptive approach. Data collection techniques through observation, interviews, and documentation. The research subjects were the principal, teachers, and parents of students. The results of this study indicate that the implementation of early childhood character education at TK Pembina 4 Ogan Komering Ulu in implementing character education uses programmed activities with the center method which is equipped with other complementary methods, namely stories, singing, fairy tales, direct practice, teacher exemplary and discussion. as well as rewards, seduction and punishment for children. Constraints in implementing character education are the competence of educators in terms of making assessment tools and RKH, the atmosphere of the school environment among educators, and the lack of assertiveness of the principal in educators not to use RKH in the learning process. Supporting factors identified include support from the community and students ‘parents.